Improving Students Mathematics Learning Outcomes Through Sundanese Ethnomathematics: A Systematic Literature Review - Permana, Neda (AB-JME: Al-Bahjah Journal of Mathematics Education, 2023)
Students’ low mathematics learning outcomes are influenced by the lack of teachers linking learning with daily life; teachers also apply conventional learning models that emphasize lectures and lectures. Ethnomathematics is a link between culture and education, especially mathematics education. Sundanese culture can be integrated into ethnomathematics, as seen from the use of non-standard units by Sundanese society. In addition, games and household appliances can be used as ethnomathematical-based problem-solving models. The method used in this study uses a qualitative library research approach with data collection techniques using a literature review. The focus of this study is the improvement of students' mathematics learning outcomes through Sundanese ethnomathematics in the fields of geometry and measurement. The results of this study stated that ethnomathematics-based mathematics learning could improve student learning outcomes and problem-solving abilities by learning, analyzing, and practicing in learning activities. Then integrating ethnomathematics indirectly can increase understanding and open new insights about local cultures, such as Sundanese culture. Thus students are expected to increase their insight into Sundanese culture and achievements simultaneously.